Analysis of Marketing Efficiency of Garlic from Nagari SalayoTanang Bukik Sileh Sub District of Lembang Jaya District of Solok - Yusri Usman (Department of Crop Science, Faculty of Agriculture, Andalas University, 2020)
This study aims to describe the marketing channel of garlic from Nagari SalayoTanang Bukik Sileh and to analyze the efficiency of the marketing channel. The study used a survey method, and data were gathered from 30 farmers who chose randomly from 103 farmers and intermediary traders. The research finds that there are four types of marketing channels of garlic in the area. The market channels are as follows: 1) Farmers → Breeders → Farmers, 2) Farmers →wholesalers→Retailers→ Consumers, 3) Farmers → Retailers (in the form of dried onions) → Consumers, 4) Farmers → Retailers → Consumers. Moreover, there is no proportional shared profit among the four marketing channels. Farmers received lower earnings than their proportionate profits, but on the other hand, the benefits received by breeders, wholesalers, and retailers were higher than their proportional profits, so that the marketing channels were inefficient.